Modelo pedagógico para la superación profesional técnica de los profesores de la rama eléctrica en el contexto de la entidad laboral - López Collazo, Zeidy Sandra (2018)
The technical professional improvement of the teachers of the electric branch, regardless of the transformations that follow, is vital to respond to the needs in the training of the technician of medium level in the specialty of Electricity and the skilled worker in the specialty of Electricity of Industrial Maintenance, becoming especially important the updating, complementation and reorientation of the professional technical content. Toward this direction the present work is addressed, in which theoretical referents are approached related to the process of improvement and presents a pedagogical model containing components and relations that harmonized with each other, contributes in a significant way to the solution of the needs of improvement Of teachers in the current conditions and requirements of Technical and Vocational Education (ETP), since it is characterized as relevant and generalizable and reveals as a novelty the relation polytechnic institute-labor, as the main feature where collaborative and interactive work Of the teachers and specialists of the labor entity. From a materialistic dialectic approach, different methods were used to elaborate the pedagogical model and its theoretical and practical validity, it was carried out through the criteria methods of specialists and users, all of which provided levels of coincidence in relation to the real possibility of to insert the teachers in the work entity taking advantage of the space of the pre-professional practices of the students.